O uso dos marcadores moleculares (p16, Ki-67 e E-Caderina) em biópsias uterinas cervicais - Munhoz, Natália Gaspar (2009)
Cervical cancer is related to the Human Papillomavirus (HPV). The E7 viral DNA sequence induces the start of DNA synthesis pf infected cell, releasing protein p16. The sequence E6 inhibits apoptosis, with prolonged survival of cells heavily damaged and changed, with inhibition of p53 protein and increasing of protein Ki-67. The E-cadherin is lost in injured cells, increasing motility cell and invade the ajacent. Objectives - to study the immunoistochemical expression of p16 protein, Ki-67 and E-cadherin in benign lesions, pre-invasive carcinoma of the cervix; to correlate the expression of these markers together in cases of difficult interpretarion, assisting in the diagnosis and prognosis of cervical lesions and asses the relationship between the expression of these markers and the persistence or not of the cervical lesion. Patients and methods: 54 uterine cervix biopsies were selected and submitted to immunohistochemical study, with biomarkers p16, Ki-67 and E-cadherin. Results: 1-CIN I (27.9%) and CIN II (47.9%) had lower expression of p16 than in CIN III (73.5%) and invasive carcinoma (72.7%) (p<0.0005). For Ki-67 There was only statistically significant difference between the median for the normal group (6.6%) with the neoplastic lesions (p=0.005). Invasive carcinoma (57.8%), was highly positive for Ki-67 when compared to CIN I (35.6%), CIN II (51.9%) and CIN III (40.9%) but the was no statistically significant difference between them. E-cadherin expression in invasive carcinoma (46.2%) was lower than in CIN III (56.0%), CIN II (77.4%) and CIN I (82.2%) (p<0.0005) and, normal epithelium had the greatest E-cadherin expression (89.1%). In persistente and no persistent CIN there was no difference in the expression of the biomarkers, with p16 presenting p=0.50, Ki-67, p=0.91 and the E-cadherin a p=0.43 value. Conclusions: there is an increased expression of p16 according to the increase in the degree of lesions. No expression in normal tissue; the Ki-67, there was greater expression of protein in cases of invasive carcinoma in the normal epithelium. However, no significant difference in expression when comparing the invasive carcinoma with CIN I, II and III and lesions of normal tissue from the cervix and CIN I showed expression of E-cadherin more pronounced, which decreases with greater severity of injury. However. there is only difference compared the expression of invasive carcinoma with CIN I and CIN II. The use of p16. Ki-67 and E-cadherin biomarkers in cervical biopsies of difficult diagnosis may help in early diagnosis of malignant lesions and support the apropriate treatment. The use of biomarkers is not useful to distinguish between persistente and non-persistente CIN.